Wheat middlings in high concentrate rations: digestibility and ruminal metabolism - B.S. Dalke; K.K. Bolsen; R.N. Jr. Sonon; Matthew A. Young (Kansas Agricultural Experiment Station Research Reports, 1995)
Six medium-framed steers, fitted with ruminal cannulae were used in a 6 x 6 Latin square design and fed the following six high concentrat e (90%) rations: control; 5, 10, or 15% pelleted wheat middlings (WM) replacing the concentrate (dry rolled corn); and 5 or 10% pelleted WM replacing the roughage (chopped alfalfa hay). Dry matter (DM), organic matter (OM), and starch digestibilities decreased linearly when increasing levels of WM replaced the concentrate , but replacing the roughage increased DM and OM digestibilities linearly. WM could replace only up to 5 % of the concentrate without reducing nutrient digestibilities, but complete (10% WM) replacement of the roughage increased nutrient digestibilities.
Keywords: Cattlemen' s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Wheat middlings; Beef cattle; Feedlot; Digestibility